2022
DOI: 10.1021/acsbiomaterials.2c00334
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Responsive Polypropylene Meshes Actuating as Thermal and SERS Sensors

Abstract: Polypropylene (PP) surgical meshes, with different knitted architectures, were chemically functionalized with gold nanoparticles (AuNPs) and 4-mercaptothiazole (4-MB) to transform their fibers into a surface enhanced Raman scattering (SERS) detectable plastic material. The application of a thin layer of poly­[N-isopropylacrylamide-co-N,N′-methylene bis­(acrylamide)] (PNIPAAm-co-MBA) graft copolymer, covalently polymerized to the mesh-gold substrate, caused the conversion of the inert plastic into a thermorespo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…[ 39 ] Copyright 2018, Springer Nature; Grafting image. [ 133 ] Copyright 2022, American Chemical Society; Free‐radical and crosslinking junctions. [ 189 ] Copyright 2018, American Chemical Society; Metal‐ion image.…”
Section: Basic Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 39 ] Copyright 2018, Springer Nature; Grafting image. [ 133 ] Copyright 2022, American Chemical Society; Free‐radical and crosslinking junctions. [ 189 ] Copyright 2018, American Chemical Society; Metal‐ion image.…”
Section: Basic Featuresmentioning
confidence: 99%
“…Reproduced with permission. [ 133 ] Copyright 2022, American Chemical Society. On the bottom right, the plot represents the effect of expansion/contraction of PNIPAAm chains, under temperature variations and increasing time, founding an LCST transition of 37 °C, 5 °C higher than the same system without AuNPs/4‐MB).…”
Section: Biomedical Emerging Applications Of Poly(n‐isopropylacrylami...mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent work, the plasma technique was employed to modify the surface polymer prostheses based on the PP matrix for incorporating a coating of the poly­( N -isopropylacrylamide) (PNIPAAm) hydrogel. , This strategy provided meshes with enhanced cell attachment and detachment modulated properties. , More recently, Learn et al also demonstrated the advantageous modification of PP meshes with cold plasma, showing that such treatment reduces fibrinogen absorption and bacteria attachment, which are both intrinsically related to the surface oxygen content.…”
Section: Introductionmentioning
confidence: 99%